Radial Nerve Neuropraxis due to Compression by C-Arm Fluoroscopy in Spine Surgery: A Case Report - João Bragança; Matthieu Hanauer; Guillaume Racloz (Case Reports in Orthopedics)
Introduction. Peripheral nerve injury is a well-known surgical complication related to the position of the patient. Moreover, in spine surgery, prone position for prolonged period places the patient at increased risk. The aim of this study was to report a case of a radial nerve neuropraxis due to compression by C-arm fluoroscopy during spine surgery. Case Presentation. An 81-year-old-female underwent a posterior spinal fixation L2-S1 due to lumbar spinal stenosis. In the recovery room, she presented an hematoma at the posterolateral part of her arm associated with a wrist drop due to radial nerve neuropraxis. The patient was referred to an occupational therapist and fully recovered four months later. After analysis of the patient positioning during the intervention, we came to the conclusion that this radial nerve injury was very possibly due to a compression by the C-arm fluoroscopy during the surgery. Conclusion. Our case describes a rare case of compression of the radial nerve during lumbar spine surgery, which is an unexpected complication as the site of the nerve injury is not at all related to the surgery itself, but to the position of the patient. Although C-arm fluoroscopy is essential, spine surgeons should be aware of this possible complication related to its use in order to avoid it.